Prevalence of valvar regurgitation in Nigerian children with structurally normal hearts using colour doppler echocardiography - Chika O Duru; Josephat M Chinawa; Igoche D Peter; Ibrahim Aliyu; Mustafa O Asani; Fidelia Bode-Thomas (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Background: Doppler echocardiography is a reliable and non-invasive method of detecting valvar regurgitation. The aim of this study was to determine the prevalence of valvar regurgitation in children with structurally normal hearts and explore its relationship with age, gender and anthropometry. Methods: This was a descriptive cross-sectional study conducted in four tertiary hospitals in Nigeria. Two hundred and thirty-three children (124 males and 109 females), from birth to 18 years were recruited prospectively. Using transthoracic echocardiography, the presence of valvar regurgitation was assessed across the four cardiac valves using Color Doppler interrogation after structural abnormalities were ruled out. Data was analyzed using the Statistical Package for Social Sciences (SPSS) software, version 22. Results: Valvar regurgitation was found in 158/233 children giving a prevalence of 67.8%. They consisted of 87 males and 71 females with a male: female ratio of 1.2:1. Of these, 82 (35.2%) had a single valvar regurgitation, 72 (30.9%) had regurgitation at two valves while 4 (1.7%) had regurgitation at three valves. Pulmonary regurgitation was the most common in 52.8% of cases while aortic regurgitation was seen in only two children (0.9%). There was a non-significant negative correlation of age and body surface area with presence of tricuspid regurgitation (ρ -0.79, p=0.22 and ρ -0.12, p=0.08) and mitral regurgitation (ρ -0.04, p=0.56 and ρ -0.02, p=0.83) but positive correlation with pulmonary regurgitation (ρ 0.11, p= 0.11 and ρ 0.12, p= 0.08). The presence of valvar regurgitation was not associated with gender (p=.>0.05). Conclusion: The prevalence of valvar regurgitation in apparently healthy Nigerian children is 67.8%. The presence of valvar regurgitation especially of the right sided valves could be a physiologic finding in apparently healthy children with structurally normal hearts. Regurgitation of the left sided valves is rare.